The Impact of The Development of Cultural Tourism On The Cultural, Economic, and Social Aspects of Local Communities - Arif Zunaidi; Nofirman Nofirman; Juliana Juliana; Rully Novie Wurarah (Universitas Trunojoyo Madura, 2022)
Development of tourism is basically aimed at the welfare of the community because the development of tourism in one area can expand employment and increase income for the surrounding local community and increase state income. But in tourism development, we must pay attention to several aspects that will be affected both by the economic and socio-cultural aspects of the surrounding local community. One of the attractions that applies the concept of cultural tourism is Kampung Naga. This research is a qualitatively descriptive study. The results of the study concluded that the development of cultural tourism in Kampung Naga has had a great impact on the local community of Kampung Naga, especially on the economic aspects of the community. In terms of the economy of the community, the level of the local community economy is better than before. The opening of new jobs and the opportunity to expand business have a positive impact on the economy of local communities. However, it also causes income inequality for the people around the dragon village. The development of tourism in Kampung Naga not only has an impact on the economic aspect but also has an impact on the socio-cultural aspects of the local community. There are several indicators that have an impact on the socio-cultural aspects of the local community.